Friendly Learning Approach in The Management of Islamic Education Institutions to Create Quality Education - Iswan Tunggal Nokgroho; Muhammad Fahmi Hidayatullah; Dian Muhammad Hakim (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
This research offers novelty by exploring the friendly learning approach in the management of quality educational institutions in sustainable development which includes adequate infrastructure, comfortable and enjoyable learning, integrated curriculum, and professional educators, a discourse that has not been widely explored. The method in this research is qualitative-descriptive with the type of case study. The results showed that Al-Mahira Junior High School designed the concept of friendly learning with a conducive, pleasant atmosphere, with various individual habituation programs and collaboration, and was designed effectively and efficiently supported by facilities, and supporting and adequate infrastructure. Integrating Islamic values into the friendly learning approach can shape the character of students who are not only intellectually intelligent, but also develop in moral and spiritual aspects. This approach can help students feel comfortable, valued, and can increase their motivation and learning achievement in a harmonious and loving atmosphere. The implementation of the friendly learning approach at Al-Mahira Junior High School is through a personalized, collaborative and flexible approach to learning. So that it has an impact on academic development and student comfort. Integration of technology and innovation in learning builds a more creative and adaptive learning atmosphere to technological advances.